AI-POWERED TOOLS IN LANGUAGE LEARNING: A STUDY OF STUDENT ENGAGEMENT AND WRITING DEVELOPMENT - Axmatova Munisa Orif qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This study explores the role of AI-powered tools in enhancing student engagement and improving writing skills in EFL contexts. It examines both the benefits and challenges of integrating artificial intelligence into language learning environments.